2019
DOI: 10.2169/internalmedicine.2035-18
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Aspects of Behçet's Disease in Japan

Abstract: Patients with Behçet's disease (BD) suffer from episodic ocular and mucocutaneous attacks, resulting in a reduced quality of life. The phenotype of Japanese BD has been changing over the past 20 years, and the rate of human leukocyte antigen (HLA)-B*51 -positive complete type is decreasing while that of intestinal type is increasing. This phenotypical evolution may be related to changes in as-yet-unknown environmental factors, as the immigration influx in Japan is low. Mechanisms discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…As shown in Tables 2 and 3 , HLA-B51 positivity was significantly less prevalent in cluster 2 (YCU) and cluster A (MHLW) than in other clusters, suggesting that the GI cluster is associated with a distinct genetic background [ 50 ]. Identification of the diverse genetic characteristics of the intestinal variant will facilitate its management as a separate disease entity [ 51 ]. Moreover, it was possible that autoinflammatory disease (AID) associated with single gene mutation had been diagnosed as BD.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Tables 2 and 3 , HLA-B51 positivity was significantly less prevalent in cluster 2 (YCU) and cluster A (MHLW) than in other clusters, suggesting that the GI cluster is associated with a distinct genetic background [ 50 ]. Identification of the diverse genetic characteristics of the intestinal variant will facilitate its management as a separate disease entity [ 51 ]. Moreover, it was possible that autoinflammatory disease (AID) associated with single gene mutation had been diagnosed as BD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HLA-B51 may not always be useful in the diagnosis of BD. 17 In several studies, it was reported that men with HLA-B51 were more at risk for BD and it was associated with early onset age. 18 However, in our study, no correlation was found between HLA-B51 positivity and age at gender and onset.…”
Section: Resultsmentioning
confidence: 99%
“…There are at least 17 diagnostic/classification criteria for BD which have various diagnostic sensitivities and specificities 7. His presentations met some of these criteria including Japanese one, and not others including International Study Group diagnostic criteria unless we regard the heel lesion as consistent with BD 8. It is still important to accumulate atypical dermatological findings of BD for further better diagnostic procedure, even though many decades have passed since the name was established.…”
Section: Descriptionmentioning
confidence: 99%